2008
DOI: 10.1016/j.ejheart.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Worsening renal function in patients hospitalised for acute heart failure: Clinical implications and prognostic significance

Abstract: Background: Renal function is a powerful prognostic variable in patients with heart failure (HF). Hospitalisations for acute HF (AHF) may be associated with further worsening of renal function (WRF). Methods and results: We analysed the clinical significance of WRF in 318 consecutive patients admitted at our institute for AHF. WRF was defined as the occurrence, at any time during the hospitalisation, of both a ≥25% and a ≥ 0.3 mg/dL increase in serum creatinine (s-Cr) from admission (WRF-Abs-%). Results: Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
260
5
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(292 citation statements)
references
References 42 publications
15
260
5
12
Order By: Relevance
“…Furosemide has been associated with worsening of kidney function in patients treated for volume overload admitted for acute heart failure (104) and even glomerular filtration rate (GFR) responses to furosemide in healthy subjects are variable (5,13,14,31,42,51,71,91,100,102,115,120,121,133,147,158,169). The very strong and short actions of furosemide have been associated with rebound sodium retention, and it has been brought to question whether furosemide would allow the reaching of a new steady state.…”
mentioning
confidence: 99%
“…Furosemide has been associated with worsening of kidney function in patients treated for volume overload admitted for acute heart failure (104) and even glomerular filtration rate (GFR) responses to furosemide in healthy subjects are variable (5,13,14,31,42,51,71,91,100,102,115,120,121,133,147,158,169). The very strong and short actions of furosemide have been associated with rebound sodium retention, and it has been brought to question whether furosemide would allow the reaching of a new steady state.…”
mentioning
confidence: 99%
“…7 Recently, several retrospective analyses from completed trials have suggested that it may be important to consider the time course of WRF and the relationship of WRF to the degree of decongestion achieved, but even in those analyses, the best outcomes are clearly in those patients who achieve clinical decongestion while preserving renal function. [8][9][10] Until a prospective trial clearly establishes that any form of WRF is safe during treatment of AHF, it is reasonable to assume that the goal of treatment should be adequate clinical decongestion without causing renal dysfunction (or worsening it if already present). Because reliance on changes in serum creatinine does not distinguish among the various causes of WRF, and because it may be important in particular to know whether true acute kidney injury occurs, the use of new biomarkers, such as cystatin C, KIM 1 (kidney injury molecule-1), and urinary natriuretic peptides, may lead to enhanced understanding of the nature and implication of mechanisms underlying WRF in future trials.…”
mentioning
confidence: 99%
“…WRF has been defined as a change in serum creatinine ≥0.3 mg/mL in most reports, a definition that has been established as the gold standard and shown to be associated with an increased risk for long‐term all‐cause/cardiovascular mortality and morbidity in AHF patients for a long time 25, 26, 27. In fact, in a retrospective study of 200 063 hospitalized AHF patients, Kociol et al .…”
Section: Discussionmentioning
confidence: 99%